Comparison of reversals in English and Vietnamese - Vo, Phuong (Ensino em Perspectivas, 2024)
Comparative research on the phenomenon of reversal in English and Vietnamese has an important role to understand the similarities and differences between these two languages in expressing messages and grammatical structures. The study will help us understand the similarities and differences of grammar and structure between these two languages. In this article, the author will use documents with 228 cases of synthesized corpus, of which English is 102 cases, Vietnamese is 126 cases. The data filtering and analysis was carried out by the author from January to October 2022. Based on the data, the author compares the phenomenon of reversal in English and Vietnamese to show similarities and differences. difference between them. After making the comparison, the author will proceed to discuss it. The experiment to evaluate its superiority will be further clarified by the author in the academic year 2023-2024 at Khanh Hoa University. The purpose of experimentation is necessary so that learners can use the language correctly and flexibly.